ANALYSIS OF BEKASI CITY REGIONAL REGULATION NUMBER 3 OF 2023 ABOUT CHILD PROTECTION - Harahap, Nur Ika Depiyanti; Djuniarsono, R. (DE'RECHTSSTAAT, 2024)
Psychosocial conditions in children and psychosocial goals are to restore individuals or families or groups after certain events (natural disasters or social disasters) so that they become strong individually or collectively; function optimally, have resilience in facing problems, and are empowered and productive in living life. Everyone has the right to participate in the planning, implementation and maintenance of programs providing health service assistance, including psychosocial support. This research aims to explain how important psychosocial is for children and to recover individuals or families or groups after certain events (natural disasters or social disasters). Everyone has the right to participate in the planning, implementation and maintenance of health service assistance programs, including psychosocial support. Psychosocial services are aimed at victims experiencing trauma and depression. Child protection in Bekasi City is still not running well, since the issuance of this Regional Regulation there are still many underage children who are employed or used to earn money such as busking, selling at red lights, begging. The government should put more emphasis on this regulation to make it better.